Recent Publications (Quarterly Journal of Economics, 1960)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 74, Issue 4, November 1960, Pages 672–674, https://doi.org/10.1093/qje/74.4.672 Published: 01 November 1960